Expreso mis emociones frente a los desastres de origen natural y desastres de origen tecnológico - Lizarraga Gutierrez, Edinson Fredy (2019)
This research paper has the title: "I express my emotions in the face of disasters"; which is designed for children in the fourth grade of primary education._x000D_ In the introduction, it is designed to class planning, the performance to be evaluated, the evidence of the learning process and the evaluation instrument to be used. Likewise, to the didactic process that is applied in the area of Social Personnel, which allows children to develop competence as a know how to combine skills, through investigative activities based on curiosity, observation and questioning, it is thus They exchange ways of thinking and contrast it with the hypotheses to build new knowledge based on their purposes._x000D_ In the second chapter the thematic body is developed according to the capacity drawn (Needs, sensations, interests and preferences), and the approaches that guide it._x000D_ In the third chapter, it is dedicated to pedagogical support, referring to psychopedagogical principles, pedagogical processes, didactic processes of the area, medium and material techniques in the methodological process, as well as evaluation procedures and instruments.